PEMBERDAYAAN KAPASITAS KEWIRAUSAHAAN KELOMPOK USAHA KECIL - Riane Johnly Pio (Universitas 17 Agustus 1945 Jakarta, 2017)
Everyone has the potential to run entrepreneurship. Moreover, if the social environment supportive of individuals who have the potential to implement a business idea into a business which is in fact there. However, only those who have personality characteristics that can be creative and innovative in carrying out the activities of entrepreneurial success. To run a business, often times individuals who have the same perspective in the business of similar form business group.This study aims to determine the entrepreneurial capacity of an existing group in the community Sonder Minahasa. Sonder communities selected as demonstrated track record since the Dutch colonial era businesses that they are tenacious and diligent in carrying out business activities. The study population was a sub-district community S onder who have entrepreneurial activity. While the samples are 68 businesses that are members of the business group in the village Ask this one. The analysis in this study using non-parametric statistics, while data collection is done through questionnaires, interviews and focus group discussions.The results showed the majority of respondents found the family economy to develop entrepreneurship is the best option, however, there are obstacles in developing the business in which more than fifty percent of the respondents have not made a good business plan, more than eighty percent of respondents stated capital as a key factor hamper business development, product marketing is often not smooth, and the price of raw materials continues to increase. The majority of respondents have not completed the training in entrepreneurship, rate high enough courage to take risks, understanding to utilize available natural resources around them pretty good environment, capital is a major constraint that is quite a big role in the success and failure in development business.To satisfy their curiosity about effective entrepreneurship need to be facilitated with training, guidance and assistance should be in the business in order to develop an entrepreneurial spirit can be realized, the courage to take a high risk should be directed to positive business activities, and socialization needs of financial institutions about the procedure to obtain capital work for all businesses.